Posyandu Financing at The District Stunting Management Locus: A Qualitative Study - Lina Rahmawati; M. Zen Rahfiludin; Martha Irene Kartasurya (Journal of Nursing Science Update (JNSU), 2023)
The prevalence of stunting among under-fives in Indonesia is still high, including in Tegal Regency, one of the loci for stunting reduction. To prevent stunting, the growth and development of children under five are monitored at integrated service posts (posyandu). Some problems in posyandu include an inadequate budget allocation for cadre incentives and the supplementary feeding program and inadequate tools and supporting facilities. This study aims to investigate posyandu funding in the district locus for reducing stunting. This research employed a qualitative approach. Data were collected by document studies and in-depth interviews using a semi-structured interview. Data saturation was achieved after involving ten informants. The informants were posyandu program holders (main informants), sub-coordinators of the Health Office, heads of the community health centre (puskesmas) from four puskesmas, i.e., two puskesmas with a high prevalence of stunting and two puskesmas with a low prevalence of stunting. Three themes were generated in this study: funding sources, funding allocations, and efforts to fulfil funding. The results revealed that posyandu funds come from the government, the business sector, and the community. Posyandu's funds are allocated for the incentives and training of cadres, the fulfilment of standardized anthropometric supporting tools and facilities, and the supplementary feeding program. Advocacy for posyandu funding was conducted through development planning meetings, Healthy Village Houses, stunting discussions, and cross-sector coordination. Overall, the variety in posyandu finance is consistent with the norms and circumstances of the locals in each area. Cross-sector cooperation must also be strengthened to address the posyandu's operational requirements.